“Then the Conscience of Humanity Arose”: Kishon and the Nations of the World - Nevo, Gidi (European journal of jewish studies, 2021)
Abstract For many years, humorist Ephraim Kishon diligently brandished his satirical whip at Israel’s socio-economic socialist structure, while vividly portraying the vicissitudes of the Israeli ‘homo economicus’ in the labyrinth of modern life. This line of writing brought him his fame, both in Israel and abroad. At the later stages of his career though, a significant portion of his work was dedicated to the relationship between Israel and its neighbors and between Israel and the world. In this area Kishon has articulated and cemented a stern nationalistic worldview. A systematic analysis of this worldview is a matter for several articles. In this article I will focus on Kishon’s treatment of national entities that are not part of Israel’s immediate circle of confrontation (i.e., its neighboring Arab states) but are rather scattered far and wide all over the world.